The Impact of the Regional Cross-Listing of Stocks on Firm Value in Sub-Saharan Africa - Adelegan, Olatundun Janet (IMF Working Papers; Working Paper ;, 2009)
This paper examines the impact of regional cross-listing on stock prices. The sample consists of sub- Saharan African firms that have cross-listed during the period 1992-2008. Using event study methodology, the study finds positive abnormal returns around the date of the regional cross-listing of stocks. The positive announcement period effect, together with the normal post cross-listing performance, shows that regional cross-listing increases firm value. Overall, this provides evidence that firms benefit from listing outside their home market and need to be taken into consideration by SSA country authorities as they seek a regional approach to stock market development. Thus, policy makers of both the countries of primary listing (home country) and secondary listing (host country) need the right policy handles to conceptualize, facilitate and steer regional cross-listing efforts by firms. Through complementary policy-based efforts, policy makers can set the stage for regional cross-listings and harness the numerous related benefits.